1991
DOI: 10.1203/00006450-199105010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Urinary Excretion of Leukotriene E4 in Children with Atopic Asthma

Abstract: MATERIALS AND METHODSbeen suggested to have an important role not only in asthma but also in other diseases, such as neonatal persistent pulmonary hypertension and acute viral respiratory infections in children (6)(7)(8). However, little is known about the role of the sulfidopeptide LT in EIA. Arterial blood sampling is considered necessary to preclude the artificial formation of these sulfidopeptide LT (9), inasmuch as the high concentrations reportedly detected in plasma derived from venous blood are probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…It was reported that there is no increase in the urinary excretion of LTE 4 up to 6 h following an exercise challenge in patients with EIA in whom there was a significant rise in urinary LTE 4 after an antigen challenge [18]. There is a significant rise in LTE 4 in children with EIA, but not in children with negative EIA [19]. Furthermore, in studies on the EIA inhibitory effects of intravenously administered MK571, which is a potent leukotriene D4‐receptor antagonist, one study prevented EIA [20], while another study did not prevent EIA [21].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that there is no increase in the urinary excretion of LTE 4 up to 6 h following an exercise challenge in patients with EIA in whom there was a significant rise in urinary LTE 4 after an antigen challenge [18]. There is a significant rise in LTE 4 in children with EIA, but not in children with negative EIA [19]. Furthermore, in studies on the EIA inhibitory effects of intravenously administered MK571, which is a potent leukotriene D4‐receptor antagonist, one study prevented EIA [20], while another study did not prevent EIA [21].…”
Section: Discussionmentioning
confidence: 99%
“…Lung diseases. In acute asthma, allergic rhinitis, and aspirinsensitive and exercise-induced asthma, elevated concentrations of LT have been recovered from biologic fluids, includingbronchoalveolar lavage, sputum, blood, and urine, spontaneously as well as after antigen challenge (43,(49)(50)(51)(52)(53) (Table 2). Clinical studies with LT receptor antagonists (see below) resulted in clinical improvement.…”
Section: Pathophysiologic Role Of Lt In Human Diseasesmentioning
confidence: 99%
“…However, the elucidation of peptide leukotriene metabolism in man [3][4][5], and the development of methodology to non-invasively measure increased in vivo 5-1ipoxygenase (5-LO) activity by monitoring elevations in levels of appropriate urinary metabolites [5][6][7], particularly LTE4 [6], has given increased credence to the hypothesis that peptidoleukotrienes are major mediators of asthmatic bronchoconstriction. Thus increased urinary LTE, excretion has been measured in acute asthma [7], antigen bronchoprovocation [6][7][8][9][10][11], aspirininduced asthma [12], exercise induced asthma [13] and nocturnal asthma [14]_ This major role for peptide LTs in asthma symptomology suggested by the above measurements of urinary LTE4 has recently been confirmed by the clinical efficacy of LTD4-receptor antagonists [15][16][17][18][19] in the above diseases. Similarly increased peptide leukotriene excretion (and a/so increased LTB4 biosynthesis in affected tissues) has been reported in a wide range of inflammatory conditions (affecting a variety of organs) such as cardiac ischemia [20,21], Adult Respiratory Distress [22][23][24], inflammatory bowel disease [25] and systemic lupus erythematosus [261.…”
Section: Introductionmentioning
confidence: 85%